Analysis of the Influence of Occupational Safety and Health on Worker Motivation for the Pramita Lab Surabaya Building Construction Project - Jenny Caroline; Hardi Abriyanto Soy; Gunawan Gunawan (Jurnal Teknologi dan Manajemen, 2024)
Construction projects are activities that are prone to work accidents and occupational diseases. Therefore, awareness of applying Occupational Health and Safety (OHS) is crucial. Basically, all humans want to complete work safely. These measures can motivate and drive workers’ behavior to carry out their work safely and healthily. This study aims to determine whether or not a correlation or influence exists between Occupational Health and Safety (OHS) and the work motivation of construction workers in the Pramita Lab Surabaya project environment. The research method was descriptive-quantitative with multiple linear regression analysis. The analysis results indicated that: (1) Based on the results of the analysis of the T-test on the work safety variable, the t-value was -0.309 critical t-value -2.042, and there was no significant effect between work safety and work motivation. (2) In the analysis of the T-test on occupational health, the value of the t-value was -4.345 critical t-value -2.042, indicating that occupational health had a significant effect on work motivation. (3) In the F-test, the calculated F-value was 27,852 F-table 3.35; Occupational Health and Safety influenced work motivation. This means that occupational safety and health is very important and affects the motivation of its workers.